Identification of Occupational Safety and Health Hazards at Paint and Welding Workshop using the HIRARC Method - Amalia, Elma Nurul; Tianisa, Berliana Noor; Nursucilowati, Luvi Lia; Rizallihadi, M. Ditra; Mahartiko, Ardheta Heru; Sabriyanti, Firda Aliya; Febrianti, Aulia; Sanda, Delyanti Pare; Nizam, Muhammad Fakrul; Widowati, Evi; Sulistyani, Ummi Nur Laila (Universitas Negeri Semarang, 2024)
Occupational Health and Safety (OHS) is important for every company to pay attention to. Preventing work accidents can be done by knowing the existing risks, one of which is through the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. Body Repair, Paint, and Welding Workshop